Critical analysis of the utility of initial pleural aspiration in the diagnosis and management of suspected malignant pleural effusion. Issue 1 (22nd September 2020) - Mercer, Rachel Mary; Varatharajah, Rebecca; Shepherd, Gillian; Lu, Qiang; Castro-Añón, Olalla; McCracken, David J; Dudina, Alexandra; Addala, Dinesh; Tsikrika, Stamatoula; George, Vineeth; Banka, Radhika; Asciak, Rachelle; et al.
Abstract : Introduction: Current guidelines recommend an initial pleural aspiration in the investigation and management of suspected malignant pleural effusions (MPEs) with the aim of establishing a diagnosis, identifying non-expansile lung (NEL) and, at times, providing a therapeutic procedure. A wealth of research has been published since the guidelines suggesting that results and outcomes from an aspiration may not always provide sufficient information to guide management. It is important to establish the validity of these findings in a 'real world' population. Methods: A retrospective analysis was conducted of all patients who underwent pleural fluid (PF) sampling, in a single centre, over 3 years to determine the utility of the initial aspiration. Results: A diagnosis of MPE was confirmed in 230/998 (23%) cases, a further 95/998 (9.5%) were presumed to represent MPE. Transudative biochemistry was found in 3% of cases of confirmed MPE. Positive PF cytology was only sufficient to guide management in 45/140 (32%) cases. Evidence of pleural thickening on CT was associated with both negative cytology (χ 2 1df=26.27, p<0.001) and insufficient samples (χ 2 1df=10.39, p=0.001). In NEL 44.4% of patients did not require further procedures after pleurodesis compared with 72.7% of those with expansile lung (χ 2 1df=5.49, p=0.019). In patients who required a combined diagnostic and therapeutic aspiration 106/113 (93.8%) required further pleural procedures. Conclusions: An initial pleural aspiration does not achieve either definitive diagnosis or therapy in the majority of patients. A new pathway prioritising symptom management while reducing procedures should be considered.